Pengaruh Pelatihan Kerja dan Kerjasama Tim terhadap Kinerja Karyawan pada PT. Astra Internasional Tbk Radio Dalam - Iman Satria Utama; Liza Nora (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of job training and teamwork on employee performance at PT Astra International Tbk, Radio Dalam Branch, South Jakarta. In today's increasingly competitive business environment, employee performance plays a crucial role in determining the success of a company. High employee performance reflects not only individual productivity but also the overall effectiveness of an organization in achieving both short-term and long-term goals. Job training serves as an essential factor in improving employee competencies, including technical skills, knowledge, and interpersonal abilities. Through well-designed and continuous training programs, employees are expected to perform their tasks more efficiently and professionally. On the other hand, effective teamwork fosters a collaborative and supportive work environment, which can enhance employee motivation and overall performance. This research uses a quantitative approach by distributing questionnaires to 60 permanent employees of the company. The data collected were analyzed using statistical techniques to examine the relationships and effects between the studied variables. The results indicate that job training has a positive and significant influence on employee performance. This means that the better the training provided, the higher the level of employee performance achieved. Additionally, teamwork was also found to have a positive and significant impact on performance. Employees who work in cohesive and well-coordinated teams tend to show higher work enthusiasm and are more capable of completing tasks effectively. Based on these findings, it can be concluded that job training and teamwork are two essential factors that management should pay close attention to. Therefore, it is recommended that the company continue to develop relevant training programs and promote a strong culture of teamwork. By doing so, the company can enhance employee performance, which in turn will help the organization achieve its objectives more efficiently and sustainably.